(untitled) (Research, Society and Development, 2020)
This is an empirical-theoretical exploratory study that uses scientific literature on architecture and school spaces. The objective is to outline a reading of the relations between architecture and education, focusing on studies that deal with architecture as an element of school spaces. Methodologically, it is a bibliographic investigation, which already takes materials/sources available and consists of a particular characteristic of documentary research. It uses digital networks and uses researches and essays published in journals linked to national databases as primary sources. Grouped into three axes of meanings (school architecture as a social project, school architecture as a didactic project, school architecture as a subjectification project), the results indicate some of the themes and concerns of the studies that deal with school architectures. It is concluded that these architectures have been the target of different investments of power and some possible fronts of future research are pointed out.